2006
DOI: 10.3177/jnsv.52.105
|View full text |Cite
|
Sign up to set email alerts
|

Sucrase-Isomaltase Gene Expression Is Inhibited by Mutant Hepatocyte Nuclear Factor (HNF)-1.ALPHA. and Mutant HNF-1.BETA. in Caco-2 Cells

Abstract: Summary Hepatocyte nuclear factor (HNF)-1 ␣ and HNF-1 ␤ are concerned in sucraseisomaltase (SI) gene expression, and directly bind two sites (SIF2, SIF3) of the promoter of the SI gene. However, it is not completely clear that HNF-1 ␣ and HNF-1 ␤ play a role in regulation of SI gene expression. To clarify mechanisms of SI gene expression regulated by HNF-1 ␣ and HNF-1 ␤ , we established four stable cell lines based on enterocyte-like cell line Caco-2, in which wild HNF-1 ␣ or wild HNF-1 ␤ , or else mutant HNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Interestingly, in our study, SI was also detected in HIEC, in contrast to the study by Perreault and Jean-François (6). Therefore, although APN and DPPIV are present on the luminal surface of both crypt and villus cells, which cannot be strictly considered as differentiation markers (33), expression of SI confirmed the differentiated character of HIEC (34). This indicated that, compared with the Perreault and Jean-François study (6), human fetal intestinal epithelial cells showed a more differentiated character in our study, although they may still belong to crypt cells.…”
Section: Discussionsupporting
confidence: 48%
“…Interestingly, in our study, SI was also detected in HIEC, in contrast to the study by Perreault and Jean-François (6). Therefore, although APN and DPPIV are present on the luminal surface of both crypt and villus cells, which cannot be strictly considered as differentiation markers (33), expression of SI confirmed the differentiated character of HIEC (34). This indicated that, compared with the Perreault and Jean-François study (6), human fetal intestinal epithelial cells showed a more differentiated character in our study, although they may still belong to crypt cells.…”
Section: Discussionsupporting
confidence: 48%
“…Additionally, in vertical sections, β1 integrin stayed in intracellular regions (presumably Golgi apparatus and granules) until Day 5, and β1 integrin was translocalized into the basolateral membrane at Day 7 (Figure 1A). Accordingly, the expression level of ALPI mRNA, a marker of epithelial cell differentiation and apical membrane (22,23), was significantly increased by Day 7 (Figure 1B). These findings demonstrated that T84 cells successfully gained morphological characteristics of differentiated epithelial cells during the 7-day culture.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatocyte nuclear factor‐1α directly binds to two sites (SIF2, SIF3) of the promoter of the SI gene and upregulates SI gene expression 21 . A reduction in SI gene expression and enzyme activity has been observed in Caco‐2 cells in which a dominant‐negative mutant of HNF‐1α was stably expressed 22 …”
Section: Discussionmentioning
confidence: 99%